Factors Associated with Emotion Regulation among Adolescent Online Game Users in Indonesia - Ely Rahmatika Nugrahani; Ah Yusuf; Sestu Retno Dwi Andayani; Ayesie Natasa Ayesie Natasa Zulka; Nurilla Kholidah; Dwi Indah Lestari (Alta Dharma Publisher, 2020)
Increasing the number of online game users in adolescence can disrupt the aspects of education, health, and social. The purpose of the study was to determine the factors that influence the emotion regulation of adolescent online game users to preventInternet Gaming Disorder. A cross-sectional study was applied in this study. We recruited 200 adolescents using multistage sampling, including 130 males and female-only 70 persons. Data were analyzed using chi-square with a significant level of p <0.05. The results of the study showed that age has a significant effect on emotion regulation of adolescent online game users with p-value 0.041 (p <0.05). The gender of online game users has a significant impact on emotion regulation with a p-value of 0.035 (p <0.05). The duration of used online games has a significant effect on emotion regulation with a p-value of 0.013 (p <0.005). The length of online game users has a significant impact on emotion regulation with a pvalue of 0.044 (p <0.05). The theme of online games has a significant effect on emotion regulation with a p-value of 0.006 (p <0.05). Online game media have a substantial impact on emotion regulation with a p-value of 0.001 (p <0.05). Emotion regulation must be increased to prevent Internet Gaming Disorder by controlling self in adolescents, especially in the adolescent male group towards the use of online games.